PARAMETRIC STUDY OF LOW VELOCITY IMPACT ANALYSIS ON CIRCULAR TUBE WITH FINITE ELEMENT METHOD - SINDHU HENDRADJAJA (NIM 13604057), SIMON
Resarch themes about vehicle safety become popular lately, as the improving of automotive engineering and the increasing of traffic intensity. One of the automotive engineering developments is a car bumper system. Car attached bumper system is to protect part of passenger compartment from frontal collision. This bumper system will absorb the impact energy of collosion through deformation process (progressive buckling). With the deformation process, bumper system can lessen damage at passanger and gives deceleration residing in at safety level to passenger body. This thesis will explain and compare about thin wall tube analysis with circular cross section and square-circular cross section comparison, this common structure used as longitudinal at car bumper system, which given low-velocity axial impact with finite element method ( LS-Dyna ). The analysis has been done by numeric using finite element method software non-linear LS-DYNA. Parametric study has been done to those circular tube to know the influence of the thickness ratio/diameter with mean crushing force. Besides of that has been done a comparison of effectivity between circular tube when absorb the energy compared by square tube with thickness ratio/with same circumference. The analysis result shows that the Pm/Mo value of circular tube is about 1.3-1.7 times larger than the Pm/Mo value of square tube. The Pm ( mean crushing force) value of circular tube is also 1.5-1.6 times larger than Pm value of square tube with the same mass ratio for 0.2 kg mass tube increment. From the analysis above, it can be concluded that the circular tube has greater capability on absorbing impact energy than the square tube. Increased on wall width thickness has large influence on increasing Pm value.